Bleeding Volume, Blood Pressure, and Consciousness Level in Association with the Mortality Rate among Patients with Intracerebral Hemorrhage at Dr. Soetomo General Hospital, Surabaya - Mohammad Pratama Jauhar Putra; Achmad Firdaus Sani; Puji Lestari; Mohammad Saiful Ardhi (Faculty of Medicine Universitas Padjadjaran, 2020)
Background: Intracerebral hemorrhage is one of the deadliest acute conditions. The volume of bleeding and its location are factors that alter consciousness level, leading to death. This study aimed to explore the association between bleeding volume, blood pressure, and consciousness level with the mortality rate among patients with intracerebral hemorrhage, so proper treatment and diagnosis can be conducted efficiently.Methods: This was an observational retrospective study conducted from October 2018–July 2019. Bleeding volume, blood pressure, consciousness level, and mortality as the outcomes of the patients with intracerebral hemorrhage were evaluated. Consciousness level was determined by using the Glasgow Coma Scale score. Data were collected from the medical record of intracerebral hemorrhage patients of the Neurologic Department in Dr. Soetomo General Academic Hospital Surabaya in the period of 2016. The Chi-square analysis method was used to determine the correlation between variables.Results: In total, 51 medical records were retrieved, and the majority of the patients were in the 45–60 years old group (54.9%). The mortality during hospitalization was 17.6% with most of them (82.4%) had bleeding volume less than 30 cc. Interestingly, the bleeding volume correlated with the consciousness level (p=0.001) and the outcome of the patients (p=0.02). The blood pressure shows a correlation with the volume of bleeding (p=0.009).Conclusions: Bleeding volume and consciousness level as determined by the Glasgow Coma Scale score show significant correlations with the mortality rate in patients with intracerebral hemorrhage.